Improving Qur'an Reading Through Tahsin-Based Learning in Primary School: Meningkatkan Kemampuan Membaca Al-Qur'an Melalui Pembelajaran Berbasis Tahsin di Sekolah Dasar - Aini, Putri Rizki; Mahariah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The ability to read the Qur'an correctly is a foundational competence for Muslim students, shaping both spiritual practice and moral development. Specific Background: However, many students, even in urban areas, struggle with tajwid and makhraj due to limited instructional time and varying support at home. Knowledge Gap: Research on the effectiveness of structured tahsin programs in non-Islamic, international-standard schools remains limited, particularly with a level-based approach. Aims: This study aims to evaluate the effectiveness of the Tahsin Program at SD Prestige Bilingual School Medan in improving students’ Qur'an reading skills. Results: Utilizing a phenomenological qualitative design, data from interviews, observations, and document analysis revealed that the implementation of talaqqi, level-based grouping, and interactive digital media significantly enhanced students’ reading fluency, tajwid accuracy, and confidence. Novelty: This study presents an innovative application of Islamic education within a non-Islamic institutional context, adapting traditional methods like talaqqi and murojaah to contemporary, multicultural learning environments. Implications: Findings suggest that a tailored, structured tahsin program can bridge academic and religious excellence, offering a replicable model for integrating Islamic learning in global educational settings.Highlight : The Tahsin Program significantly improves students' ability to read the Qur’an correctly, especially in tajwid and makhraj. A level-based system ensures personalized learning that matches students' current reading abilities. Teacher competence and media support (like digital tools) enhance the effectiveness and engagement of the learning process. Keywords : Qur'an Reading Ability, Method, Tahsin Program, Tajwid, Makhraj